2020
DOI: 10.1155/2020/6398520
|View full text |Cite
|
Sign up to set email alerts
|

Association of Oxidative Stress on Pregnancy

Abstract: The pathophysiological mechanism underlying pregnancy complications such as congenital malformations, miscarriage, preeclampsia, or fetal growth restriction is not entirely known. However, the negative impact of the mother’s body oxidative imbalance on the fetus and the course of gestation is increasingly discussed. This article is an integrative review of some original studies and review papers on the effects of oxidative stress on the adverse pregnancy outcomes mainly birth defects in fetuses. A systematic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 51 publications
1
61
0
5
Order By: Relevance
“…The pathophysiological mechanisms of many diseases and complications of pregnancy are not well understood. However, studies have shown that oxidative stress is involved in most maternal and fetal complications (e.g., miscarriage, preeclampsia, fetal growth restriction, and preterm labour) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological mechanisms of many diseases and complications of pregnancy are not well understood. However, studies have shown that oxidative stress is involved in most maternal and fetal complications (e.g., miscarriage, preeclampsia, fetal growth restriction, and preterm labour) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both physiological and pathological communications can be mediated between the mother and the fetus via exosomes. Since all uterine cells constantly secrete exosomes, their cargo is likely involved in maintaining balanced tissue functions 45,46 . Pathological changes to cells, in response to endogenous or exogenous factors during pregnancy, produce exosomes that are capable of causing a parturition-associated fetal in ammatory state through delivery of pro-in ammatory mediators 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Pada awal kehamilan, plasenta sangat vaskuler dan terpapar tekanan oksigen arteri yang tinggi dari ibu. Akibatnya, plasenta meningkatkan produksi ROS (Toboła-Wróbel et al, 2020). Pada kehamilan, metabolisme dan metal transisi seperti Cu akan meningkat.…”
Section: Pendahuluanunclassified
“…Berkebalikan dengan kadar Cu, kadar MDA trimester II lebih tinggi dibanding trimester III (p<0,05). Hasil ini sesuai dengan penelitian terdahulu (Toboła-Wróbel et al, 2020) yang menyatakan bahwa level lipid peroksidasi serum meningkat pada wanita hamil normal, mencapai konsentrasi maksimal pada trimester II, kemudian menurun sampai ke level yang sama dengan trimester I. Kehamilan merupakan kondisi yang rentan terjadi stres oksidatif. Kerentanan ini berhubungan dengan produksi enzim NAD(P)H Oksidase dan Xantin Oksidase oleh plasenta, plasenta yang kaya mitokondria serta perubahan fisiologik dan metabolik kehamilan yang semuanya meningkatkan produksi ROS.…”
Section: Gambar-2 Ringkasan Lokasi Peran Cu Sebagai Antioksidanunclassified
See 1 more Smart Citation